Bluey : Unicorse. - Penguin Young Readers Group (Penguin Young Readers Licenses, an imprint of Penguin Random House LLC, 2024)
"Unicorse is the most annoying unicorn in the world, but can Bluey make him behave?" --
Bluey doesn't want to go to bed, so Mum decides to read her a story, when they're interrupted by Unicorse, the most annoying unicorn in the world. Will Bluey and Mum finish the bedtime story?
At head of title: Bluey.
"First published in Australia by Puffin Books, 2023"--Title verso page.
"This book is based on the TV series Bluey."--Title page.
Ages: 3-5.
GN520L
Keywords: Bluey -- (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Bedtime -- Juvenile fiction; Unicorns -- Juvenile fiction; Hand puppets -- Juvenile fiction; Picture books